2020
DOI: 10.3390/su12093933
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Impact of Residential Outdoor Environments on Mood in the Elderly in Guangzhou, China

Abstract: Understanding the relationship between mood and the environment among the elderly is important for the healthy aging agenda. This study aimed to investigate the relationship between residential outdoor environments of different qualities and mood in the elderly. Nine residential neighborhoods across three different quality levels of the outdoor environment in Guangzhou, China, were surveyed. Measures included demographic characteristics, assessment of the residential outdoor environment, and mood status of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 96 publications
(123 reference statements)
0
17
0
1
Order By: Relevance
“…For the elderly, those living in low-quality housing have a stronger demand for green space. They are more likely be affected by light, smell, greenness, temperature, and humidity [95].…”
Section: The Heterogenous Effect Of Environmental Factormentioning
confidence: 99%
“…For the elderly, those living in low-quality housing have a stronger demand for green space. They are more likely be affected by light, smell, greenness, temperature, and humidity [95].…”
Section: The Heterogenous Effect Of Environmental Factormentioning
confidence: 99%
“…Furthermore, a growing body of study has suggested that a built environment is related to traits of psychological well-being such as mood, anxiety, and depression [ 33 , 34 , 35 ]. For example, Wang et al found that older people living in a walkable community were more likely to report a positive mood than those who are living in a community with poor walkability [ 36 ].…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…Pacione analyzed the impact of personal and family characteristics such as age, income, education and physical health on mental health [ 9 ]. In addition, many research studies have considered the impact of green landscape on the emotions of the elderly [ 14 , 15 , 16 , 17 , 18 ]. Chen Chongxian found that different quality environments in built residences have different influencing factors on the emotion of the elderly [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many research studies have considered the impact of green landscape on the emotions of the elderly [ 14 , 15 , 16 , 17 , 18 ]. Chen Chongxian found that different quality environments in built residences have different influencing factors on the emotion of the elderly [ 14 ]. Grahn and Zhou Suhong reported that the community environment affects residents’ way of thinking and behaviour, thus affecting their mental health [ 15 , 18 ].…”
Section: Introductionmentioning
confidence: 99%